Butterfly phenology in Mediterranean mountains using space‐for‐time substitution - Konstantina Zografou (Wiley, 2020)
Abstract Inferring species' responses to climate change in the absence of long‐term time series data is a challenge, but can be achieved by substituting space for time. For example, thermal elevational gradients represent suitable proxies to study phenological responses to warming. We used butterfly data from two Mediterranean mountain areas to test whether mean dates of appearance of communities and individual species show a delay with increasing altitude, and an accompanying shortening in the duration of flight periods. We found a 14‐day delay in the mean date of appearance per kilometer increase in altitude for butterfly communities overall, and an average 23‐day shift for 26 selected species, alongside average summer temperature lapse rates of 3°C per km. At higher elevations, there was a shortening of the flight period for the community of 3 days/km, with an 8.8‐day average decline per km for individual species. Rates of phenological delay differed significantly between the two mountain ranges, although this did not seem to result from the respective temperature lapse rates. These results suggest that climate warming could lead to advanced and lengthened flight periods for Mediterranean mountain butterfly communities. However, although multivoltine species showed the expected response of delayed and shortened flight periods at higher elevations, univoltine species showed more pronounced delays in terms of species appearance. Hence, while projections of overall community responses to climate change may benefit from space‐for‐time substitutions, understanding species‐specific responses to local features of habitat and climate may be needed to accurately predict the effects of climate change on phenology.